Mobile application: career pathway recommendation system for pure science student / Nor Farhana Sulaiman - Sulaiman, Nor Farhana (2022)
Students are often faced with the challenge of deciding on a career path. This study will develop a mobile application system and utilize the internet to use it for the career pathway recommendation system. The accuracy of this system is important to ensure the career are match with the students' academic achievements The project aims to develop career pathway recommendation system for student. To develop career pathway recommendation system for student, this project decided to use ANN technique with the features of mobile application system, based on academic result. The technology will be mobile application which convenience for the student to access the system in their gadget. Flutter will be used to develop the mobile application, with ready to use widgets, it will be fast development.